NEW WELDING EQUIPMENT AT OAO «MMZ» – QUALITY AND ENERGY SAVING - V. M. Gatsuro; G. E. Mayauskas (Литьë и металлургия)
The is information on qualitative indices of new equipment for production of longitudinal tubes in the article. Analysis of economical grounds of its implementation and the received economical effect on energy conservation is given.